Response of fenugreek (Trigonella foenum-gracecum L.) to sodicity - V K, Garg (Journal of Spices and Aromatic Crops, 2012)
Field trials were conducted at Lucknow (Uttar Pradesh) to study the effect of sodicity on growth, yield and cation composition of fenugreek (Trigonella foenum-graecum L.). The treatments included five exchangeable sodium percentage (ESP) levels (10, 20, 30, 40 and 50) and four varieties namely, HM-346, RMt-1, Hissar Sonali and Kalyanpur Selection. The results showed that the crop was able to endure sodicity at germination stage but an adverse effect was noticed on emergence of branches plant-1 rather than plant height. The yield attributes were unaffected up to ESP 30. The variety Kalyanpur Selection produced greater biomass and seed yield than other genotypes up to ESP 30. The cation composition of plant revealed Na inclusion mechanism and showed narrow K/Na and Ca/Na ratio in the foliage indicating the potential of fenugreek crop to withstand medium level of sodicity.